BS ISO 23906-1. Cigarettes. Determination of benzo[a]pyrene in cigarette mainstream smoke under intense smoking conditions using GC/MS. Part 1. Method using methanol as extraction solvent (3rd December 2019) - British Standards Institution,
No abstract available